International indicators on youth education attainment levels - what is Germany's true position? - Pfeifer, Harald [Verfasser]; Müller, Normann [Verfasser] (My University, 2009)
"Altough indicators mapping the level of youth education attaiment in international comparative terms are often used in discussions centering on the efficiency and effectiveness of the German eudcational system, the position occupied by Germany is not clear. The Eurostat data, for example, shows that the proportion of young people who have at least completed upper secondary educatin is at a comparatively low level. This contrasts with the upper secondary education completion rates provided by the OCED, where the figures for 2006 (OECD, 2008) show Germany in top position. The aim of the following is to examine the computation approaches adopted by both indicators and the attendant interpretation problems more closeley." (Autorenreferat, BIBB-Doku)
Keywords: G 1.2.3.1 Potenziale; G 1.1.4 Statistiken zu speziellen Problemlagen & Bereichen; T 3.5 Statistik; Bildungsniveau; Jugendlicher; Indikatoren; Bildungsabschluss; Quote; Bildungsstatistik; Statistische Methode; Internationaler Vergleich